2020
DOI: 10.3390/ani10010087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Behavioural Indicators of Calf Discomfort Following Routine Procedures on Cow Maternal Care

Abstract: Pain causes altered arousal and specific behaviours that are rare at other times (pain indicators). We examined whether beef cows (mean age 6 years) are sensitive to pain indicators in addition to arousal following ear tagging and rubber ring castration (males only, n = 31) of their calf (n = 58). Behavioural pain indicators and activity were recorded continuously for 20 min before and 2 h after handling. The 30 min period posthandling captured the peak of behavioural change during this window. Cow maternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…Our results are in contrast with findings of Ede et al who reported that calves spent more time in proximity to a conspecific in pain 47 , and Gingerich et al who even reported decreased interest of disbudded calves in sharing shelter with other calves 6 . Our results are consistent with the findings of Turner et al who did not confirm increased maternal care towards calves displaying the most behavioral evidence of pain 48 . Taken together, further research is needed to investigate what quantity and which types of social interactions are effective for transmission of social buffering.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in contrast with findings of Ede et al who reported that calves spent more time in proximity to a conspecific in pain 47 , and Gingerich et al who even reported decreased interest of disbudded calves in sharing shelter with other calves 6 . Our results are consistent with the findings of Turner et al who did not confirm increased maternal care towards calves displaying the most behavioral evidence of pain 48 . Taken together, further research is needed to investigate what quantity and which types of social interactions are effective for transmission of social buffering.…”
Section: Discussionsupporting
confidence: 93%
“…Ede et al reported that calves spent more time in proximity and paid more attention to a conspecific in pain compared to a sham treated calf 47 . However, Gingerich et al reported that disbudded calves left shelter more frequently when it was occupied 6 , and Turner et al reported that ear tagging and castration did not result in calves receiving more maternal attention 48 . Therefore, our second objective was to investigate whether pair-housed calves increase social contact after disbudding.…”
Section: Introductionmentioning
confidence: 99%
“…The farm was divided into five production units, three of them dedicated strictly to cow-calf operation, as described by Costa et al [16]. Animal assessment and data collection were carried out in only two units, in which second and third parity cows (U2) and those with three or more parity (U4, multiparous) were kept.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, MPB can be used as an indicator of bonding between the cow and her calf, playing an important role in the success of calf survival [12,13] and is characterized by an increased level of the cow's aggressiveness towards potential predators (including cowhands) when in the presence of her calf [14]. In this sense, a cow's reaction towards cowhands when handling their newborn calf can be assessed and used as an indicator of MPB [15,16], assuming that, under such context, apathetic (those which do not react) and fearful cows (those which try to escape) indicate low maternal investment in their calves, which can probably lead to a higher risk of calf death [17,18].…”
Section: Introductionmentioning
confidence: 99%